Social suppression of reproduction in the naked mole-rat, Heterocephalus glaber : -Plasma LH concentrations and differential pituitary responsiveness to exogenous GnRH - Van der Westhuizen, Laura-Ann (Department of Biological Sciences, 2016)
Bibliography: pages 104-111.